Pretreatment and improvement of bonding strength of self-adhesive resin cements to posts - Luis Rafael Calixto; Mateus Rodrigues Tonetto; Matheus Coelho Bandéca; Eduardo Fernandez; Alain Manuel Chaple Gil; Edson Alves de Campos; Marcelo Ferrarezi de Andrade (Editorial Ciencias Médicas, 2019)
Introduction: Posts and core are frequently used in endodontically treated teeth with excessive loss of coronal tooth structure. Objective: To evaluate the effectiveness of self-adhesive cements under different pre-treatments of dentin in the resistance to extrusion of fiberglass posts. Methods: An experimental in vitro study was conducted. The randomly selected sample was 56 extracted bovine incisors with mature apices and without root curvature. Before the cementing procedure, pretreatment of dentin was performed with 11.5 % polyacrylic acid, 17 % EDTA or sodium hypochlorite. The type of failure between the post/cement/dentin was evaluated by stereomicroscope. Two hundred and sixteen bovine dentin discs were used. The disks were approximately 1 mm thick, and were obtained from 72 bovine roots restored with intraradicular retentions. Data were analyzed for better comprehension in an SPSS database for Windows version 15. Results: The highest values were found in groups G3, G4 and G5, and there was no bond strength significant difference in group G2. Conclusions: The pre-treatment had no effect on dentin bond strength, and the self-adhesive cement RelyX U100 appears to be a viable option in the cementation of fiber posts.